Changing Nature of Health Crisis from Infectious Diseases and Responses Over Three Decades in Malaysia - Arif, Mohamad Taha (Borneo Journal of Resource Science and Technology, 2016)
The author relates his 35 years experiences serving the public health sector in various capacities at district, state and country levels in Malaysia. He described several important outbreaks encountered such as malaria, dengue, cholera, enterovirus encephalitis, Nipah virus encephalitis, avian influenza, SARS and leptospirosis. He discussed the determinants of infectious diseases outbreak such as the pathogenicity of the organism, the environmental factors, human and animal factors. The impact of these outbreaks affected the economy, psychosocial, political and international relations. The responses to these outbreaks had improved along with the development of new technologies in diagnosis, surveillance, information technology and human resource development. The author also identified the importance of networking, appropriate risk and crisis communication and the management of the after effect of the outbreak. Apart from outbreak preparedness plan, research remains an important tool in discovering new diseases and appropriate ways of responding to the crisis.